ANALYSIS OF THE CURRENT CONDITIONS ON THE COST OF RAILWAY TRANSPORTATION OF UKRAINE - Kalambet, S. V.; Pryvalova, L. V.; Pyvniak, Yu. V.; Dronov, S. Y. (Science and Transport Progress, 2007)
The progressive aging of the railways capital assets, modernization of infrastructure requirements, lack of state support in the innovative development of a branch, low rates for the carriage of passengers. This leads to their cross-subsidization at the expense of freight cargo. These facts caused the Ukrainian railways reforms. The impact of current conditions on the railroading cost in Ukraine was analyzed in the article.